2010
DOI: 10.1186/1749-799x-5-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low power laser irradiation on bone healing in animals: a meta-analysis

Abstract: PurposeThe meta-analysis was performed to identify animal research defining the effects of low power laser irradiation on biomechanical indicators of bone regeneration and the impact of dosage.MethodsWe searched five electronic databases (MEDLINE, EMBASE, PubMed, CINAHL, and Cochrane Database of Randomised Clinical Trials) for studies in the area of laser and bone healing published from 1966 to October 2008. Included studies had to investigate fracture healing in any animal model, using any type of low power l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 33 publications
1
39
0
1
Order By: Relevance
“…Previous studies have demonstrated the beneficial effects of LLLT on bone repair in experimental models of DM 12,13 . However, many other controversial data have been reported in the literature concerning the modulatory effect of LLLT on bone healing in diabetic animals, likely as a result of the variety of threshold parameters for energy density and intensity, including the irradiation time and the irradiation mode, used in the experiments 14,15 . Therefore, the purpose of this study was to assess the effect of a protocol of low-level laser therapy using diode GaAlAs laser on the bone repair in alloxan-induced diabetic rats.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the beneficial effects of LLLT on bone repair in experimental models of DM 12,13 . However, many other controversial data have been reported in the literature concerning the modulatory effect of LLLT on bone healing in diabetic animals, likely as a result of the variety of threshold parameters for energy density and intensity, including the irradiation time and the irradiation mode, used in the experiments 14,15 . Therefore, the purpose of this study was to assess the effect of a protocol of low-level laser therapy using diode GaAlAs laser on the bone repair in alloxan-induced diabetic rats.…”
Section: Introductionmentioning
confidence: 99%
“…The graded structure of the enthesis appears to be optimized to achieve an effective load transfer (Liu et al 2012; Genin et al 2009). However, this optimized interface is not re-formed after injury, leading to poor healing outcomes, presumably due to concentrations of stress at the interface (Lui et al 2010; Harryman et al 1991; Galatz et al 2004). Our paper examines mechanical loading on the developing enthesis structure over time, offering an understanding of mechanical factors that may be important for the development, homeostasis, and healing of a functional enthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Low power LASER devices have little to no thermal effects and are used to treat an array of musculoskeletal conditions to decrease pain, inflammation and soft tissue scars, and to promote fracture healing [34, 43-45]. Three main types of LASER are used clinically: helium-neon (HeNe wavelength 632.8nm, tissue penetration 0.8mm), the gallium-arsenide (GaAs 904nm, penetrating 5cm) and the gallium-aluminum-arsenide (GaAlAs 830nm, penetrating 2-3cm) [34, 43].…”
Section: Lasermentioning
confidence: 99%